2020
DOI: 10.2174/1574885515666200305101840
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Comparative Study of Different Brands of Metoclopramide Hydrochloride Tablets Marketed in Saudi Arabia

Abstract: : Metoclopramide hydrochloride (MCP) a derivative of paraminobenzoic acid, freely soluble drug, rapidly absorbed from the gastrointestinal tract and is used in the management of gastrointestinal disorders such as gastric stasis, gastroesophageal reflux and for the prevention of cancer chemotherapy induced emesis. Many different brands of MCP are available in Saudi Arabia. Objectives: The objective of present study was to evaluate the four brands of MCP 10mg tablets (Premosan, Primperan, Maxolon and Metoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Typically, oral tablets exhibit a hardness range of 4 to 10 kg according to non-official USP specifications. 28 The result of the hardness test in this study showed that all brands failed the non-official test with M1 having the least hardness of 15.325±0.82 Kg and M4 having the highest hardness of 23.588±1.91 Kg. ( Table 4 )…”
Section: Resultsmentioning
confidence: 62%
“…Typically, oral tablets exhibit a hardness range of 4 to 10 kg according to non-official USP specifications. 28 The result of the hardness test in this study showed that all brands failed the non-official test with M1 having the least hardness of 15.325±0.82 Kg and M4 having the highest hardness of 23.588±1.91 Kg. ( Table 4 )…”
Section: Resultsmentioning
confidence: 62%